Micronutrient losses during renal replacement therapy for acute kidney injury - Oh, Weng Chin (2017)
Malnutrition is common in acute kidney injury (AKI) patients, particularly on the ICU, where they often receive renal replacement therapy (RRT). RRT may exacerbate loss of water-soluble micronutrients (e.g. trace elements, amino acids and B-vitamins). No clinical study has quantified these losses and contrasted between types of RRT that use different methods to remove solutes i.e. by diffusion (intermittent haemodialysis, IHD) by convection (continuous veno-venous haemofiltration, CVVH) or by a combination of both (sustained low-efficiency diafiltration, SLEDf).